Impact of the 'Learning from Excellence' programme in NHS trusts: an exploratory study. Issue 8 (2nd August 2020) - Kletter, Maartje; Plunkett, Emma; Plunkett, Adrian; Hunt, Helen; Bird, Paul; Brown, Celia
Abstract : Background/Aims: The 'Learning from Excellence' (LfE) programme aims to provide a means to identify, appreciate, study and learn from episodes of excellence in frontline healthcare. The aim of this study was to explore the impact of LfE on organisational performance in NHS trusts in the United Kingdom (UK), how this impact is achieved and which contextual factors facilitate or hinder impact. Methods: A survey and case studies, including individual interviews, were conducted. Data were analysed through qualitative content analysis, informed by realist evaluation methodology. Contextual factors, mechanisms and outcomes were coded, sub-themes were generated and a programme theory was developed. Results: There were 47 respondents to the survey (27% response rate) and three case studies were performed. A total of 25 contextual factors were identified, of which 18 acted as a facilitator to uptake or as a barrier if absent. Additionally, 11 mechanisms and 9 outcomes were identified. A programme theory explaining how LfE can impact organisational performance in NHS trusts in the UK, and which contextual factors play a role before design, during design and during implementation, was developed. Conclusions: LfE was welcomed by participants, but at the time of this study LfE had not been implemented for long enough for outcomes to be measured. Further research, particularly measuring outcomes and validating mechanisms, as well as exploring the learning based on reported events, is needed.